Growth, maturation, functional capacities and sport-specific skills in 12-13 year-old- basketball players - Coelho e Silva, M. J.; Moreira Carvalho, H.; Gonçalves, C. E.; Figueiredo, A. J.; Elferink-Gemser, M. T.; Philippaerts, R. M.; Malina, R. M. (The Journal of Sports Medicine and Physical Fitness, 2010)
AIM: The influence of maturity status on body size, functional capacities and basketball-specific skills was evaluated and multivariate relationships between domains of variables were examined in 80 male basketball players 12.0-13.9 years. METHODS: Height, body mass and two skinfolds were measured. Stage of pubic hair (PH) was assessed clinically. Functional capacity was assessed with the vertical jump (squat jump, countermovement jump), 2-kg medicine ball throw, hand grip strength, 60-second sit-ups and endurance shuttle run. Performances on four basketball skills were tested: shooting, passing, dribbling and defensive movements. Analysis of covariance with age as the covariate was used to test differences among players by stage of puberty. Associations among body size, adiposity, functional capacities and skills were evaluated with canonical correlation analysis. RESULTS: Maturity status explained a significant portion of variance in body size (F=50.13, P<0.01, h2=057, for height; F=13.47, P<0.01, h2=0.26, for weight). The effect of pubertal status was significant for the jumps and upper limb strength, but not for sit-ups or aerobic endurance. Canonical correlations showed an inverse relationship of height and adiposity with skill tests, and a positive relationship between skills and a combination of abdominal muscular strength (sit-ups) and aerobic endurance. CONCLUSION: Skill appeared to be independent of pubertal status and the tallest group of basketball players did not attain better scores in basketball-specific skill tests.